2003
DOI: 10.1038/oby.2003.92
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Dietary and Exercise Stage of Change to Optimize Weight Loss Interventions

Abstract: Res. 2003;11:641-652. Objective: According to the Transtheoretical Model (TM), tailoring interventions to patients' readiness to change can enhance patient progress and help patients use therapeutic resources more effectively. However, tailoring an intervention depends on accurate assessment of patients' stage of change (SOC). This study describes a multi-item algorithm of SOC (M-SOC) for weight loss-related behaviors that attempts to overcome some of the conceptual and methodological difficulties encountered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 36 publications
(44 reference statements)
0
67
0
9
Order By: Relevance
“…Other instruments have been validated regarding GMP (Akutsu, Botelho, Camargo, Oliveira, & Araújo, 2005;Araújo et al, 2015;Santos, Akutsu, Botelho, & Zandonadi, 2012), instruments to determine the readiness for change stage (Cattai, Hintze, & Junior, 2010a;Sutton et al, 2003), and to evaluate the understanding, knowledge, attitudes and practice obtaining an overall confidence interval of 95% (Cunha, Stedefeldt, & Rosso, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other instruments have been validated regarding GMP (Akutsu, Botelho, Camargo, Oliveira, & Araújo, 2005;Araújo et al, 2015;Santos, Akutsu, Botelho, & Zandonadi, 2012), instruments to determine the readiness for change stage (Cattai, Hintze, & Junior, 2010a;Sutton et al, 2003), and to evaluate the understanding, knowledge, attitudes and practice obtaining an overall confidence interval of 95% (Cunha, Stedefeldt, & Rosso, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Step 1 -Instrument Creation, Validation and Testing For the creation of the ACSFH, routine activities of the food handlers were used, as well as procedures that are present in the Brazilian current food safety legislation, RDC 216/2004 , and a literature survey to define the initial constructs of the attitude change stage (Cattai, Hintze, & Junior, 2010b;Cuprasitrut, Srisorrachatr, & Malai, 2011;Egan et al, 2007;Rahman, Arif, Bakar, & bt Tambi, 2012;Sutton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…O Modelo Transteórico também vem sendo utilizado em intervenções como uma ferramenta para medida da prontidão dos sujeitos para a mudança em comportamentos de risco à saúde (MARSHALL, BIDDLE, 2001;NAHAS et al, 2009;SUTTON et al, 2003). Nestes casos, o objetivo principal é auxiliar a compreensão acerca dos processos de mudança e, desta maneira, tornar mais efetivas as intervenções.…”
Section: Introductionunclassified
“…Because of the ambiguity of constructs such as ''eating a low-fat diet'' or ''increasing physical activities,'' assessing stage of change for weight loss and related behaviors has presented methodological and conceptual challenges. 12,22 Most studies develop and use different algorithms and items making results difficult to compare across studies. Earlier studies found different stage of change distributions for weight loss, diet, and exercise than our study.…”
mentioning
confidence: 99%
“…While patients at earlier stages may benefit from counseling about the harms of their current behaviors and the benefits of change, patients in the preparation, action, and maintenance stages may be more receptive to advice about specific strategies to effect or sustain behavior change. 11,12 Counseling about weight loss includes advice about weight loss, diet, and exercise. Assessing stage of change for multiple weight-related behaviors can be time consuming in clinical practice.…”
mentioning
confidence: 99%